Discourse on Religious Moderation in the North Sumatra Baznas Media: Critical Linguistic Analysis Based on the Principles of Maqāṣid al-Sharī'ah - Siregar, Umar Mukhtar (Jurnal Bahasa Indonesia Prima (BIP), 2026)
This study analyzes the discourse of religious moderation constructed in the digital media language of the National Zakat Agency (BAZNAS) of North Sumatra Province, as reflected on its official platform at sumut.baznas.go.id. Using a Critical Discourse Analysis (CDA) approach, this study examines the official posts of BAZNAS North Sumatra for the 2025–2026 period. The evaluative framework of Maqāṣid al-Sharī'ah—which includes safeguarding religion (ḥifẓ al-dīn), soul (ḥifẓ al-nafs), intellect (ḥifẓ al-'aql), descendants (ḥifẓ al-nasl), and wealth (ḥifẓ al-māl) is used integratively to evaluate the welfare orientation of the discourse practices found. The analysis reveals six main linguistic mechanisms that shape the architecture of BAZNAS North Sumatra's moderation discourse: (1) the naturalization of ideology through the three-element slogan "Safe Syar'i, Safe Regulation, and Safe NKRI"; (2) the reframing of the meaning of zakat from ritual worship to a socio-economic policy instrument; (3) dual intertextuality that presents the authority of sacred texts and state regulations simultaneously; (4) the formation of a moderate identity through contextual associations with state counter-terrorism institutions and the construction of an implicit enemy; (5) a structured gradation of modalities—high deontic for norms, low epistemic for claims of results—as a reflection of a firm yet humble ideological position. The maqāṣid reading of these five mechanisms shows that BAZNAS North Sumatra's digital discourse simultaneously realizes all five maqāṣid dimensions and mutually supports them, with ḥifẓ al-dīn and ḥifẓ al-nafs as the most dominant dimensions.